Description of Anaplectus jilinicus sp. nov. (Nematoda: Chromadorea: Plectidae), a new nematode species from Jilin Province, Northeast China, with a Key to the Species of the genus Anaplectus - Hussain, Sagir; Zuo, Junqi; Guan, Pingting; Wu, Donghui (Zootaxa, 2026)
In a comprehensive survey of nematodes, a new species, Anaplectus jilinicus sp. nov. was described using soil materials collected from Jilin province, Northeast China. Information of molecular and morphometric characterization, beside measurements, illustrations, and light microscopy pictures, host records for Anaplectus jilinicus sp. nov. from Jilin province, Northeast China, were provided. The species is characterized by females 1024–1236μm long with a 20–27μm stoma, six separate lips 10–12μm in diameter, amphidial openings 8–14μm from the anterior end, pharynx 203–266μm, V% = 49–53, vulva 534–656μm from the anterior end, and a 60–80μm elongate-conoid tail with functional spinneret; males are 1002–1196μm long with a spicule 41.7–44.1μm and gubernaculum 11.9–13.9μm. The phylogenetic analysis of the new species using 28S rDNA and D2-D3 segments of the ribosomal DNA gene is placed in a clade with 0.7 posterior probability values with the other species of Anaplectus. In addition, 28S rDNA showed a 99% similarity with A. deconincki from South Africa (OM905072) and a 99% similarity with A. granulosus from Germany (MF325169). Discriminant analysis clearly separated A. jilinicus sp. nov. from the other related species of the genus. An emended generic diagnosis, a complete species list, and an updated identification key are provided for all 22 currently recognized Anaplectus species, including the newly described Anaplectus jilinicus sp. nov.